The Challenges in Developing Smart Tourism: A Literature Review - Teguh Iman Pribadi; Rusdin Tahir; Ayu Krishna Yuliawati (Universitas Islam Sumatera Utara, 2021)
Smart tourism is experiencing rapid development along with the information and communication technology (ICT) revolution. ICT has enabled companies engaged in tourism to be